RANCANG BANGUN SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERBASIS WEB PADA PT JALA LINTAS MEDIA - Nurdiansyah (2021)
In a commercial company, customers are the target of providing goods and services by a company. Including PT Jala Lintas Media, which is a telecommunication service company, especially in the internet sector, that always puts customers first. Customer Relationship Management (CRM) information systems can be a solution to help manage customer data so that the quality of service to customers increases. Research conducted for seven months in 2020 on PT Jala Lintas Media resulted in a CRM information system built using the Waterfall method based on the results of the PIECES analysis on the running system. The proposed web-based system which has features such as data management and complaints will assist PT Jala Lintas Media in improving service quality. Thus it will provide more value to the relationship between the company and customers. Keywords: Information System, Customer Relationship Management, Customer